OBTAINING AND TESTING RESULTS OF PF-1 BRAND CORROSION INHIBITOR OBTAINED BASED ON THE PROCESSING OF CHLORINATED ORGANIC WASTE USED IN THE OIL AND GAS INDUSTRY - Avazov Mirjalol Shukhrat ugli; Khalilov Jamshid Akmal ugli; Nurkulov Fayzulla Nurmuminovich (European Science Publishing, 2024)
The article examines the physical and chemical properties of corrosion inhibitors obtained on the basis of the processing of organochlorine waste for the oil and gas industry. Corrosion inhibitors of metals were obtained as a result of the synthesis and their level of protection was checked. The results of IR and NMR spectra were studied.
Keywords: Corrosion inhibitors, nitrogen, organic compounds, fatty acids, gas-condensate well, temperature, mass, level of protection.